2000
DOI: 10.1021/bi992474k
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Kinesin Activity from Structure-Based Computer Screening

Abstract: Kinesin motor proteins use ATP hydrolysis for transport along microtubules in the cell. We sought to identify small organic ligands to inhibit kinesin's activity. Candidate molecules were identified by computational docking of commercially available compounds using the computer program DOCK. Compounds were docked at either of two sites, and a selection was tested for inhibition of microtubulestimulated ATPase activity. Twenty-two submillimolar inhibitors were identified. Several inhibitors appeared to be compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 43 publications
3
54
0
Order By: Relevance
“…To selectively impair MT-based motors, we used the wellestablished dynein inhibitor EHNA (Penningroth et al, 1982;Reynolds et al, 1998) and the kinesin inhibitor aurintricarboxylic acid (AA) (Hopkins et al, 2000). AA has been recently identified via a structure-based computer screening for kinesin-binding molecules using human conventional kinesin as template (Hopkins et al, 2000).…”
Section: Efficient Tent Hc Retrograde Transport Relies On Multiple Mtmentioning
confidence: 99%
See 1 more Smart Citation
“…To selectively impair MT-based motors, we used the wellestablished dynein inhibitor EHNA (Penningroth et al, 1982;Reynolds et al, 1998) and the kinesin inhibitor aurintricarboxylic acid (AA) (Hopkins et al, 2000). AA has been recently identified via a structure-based computer screening for kinesin-binding molecules using human conventional kinesin as template (Hopkins et al, 2000).…”
Section: Efficient Tent Hc Retrograde Transport Relies On Multiple Mtmentioning
confidence: 99%
“…To selectively impair MT-based motors, we used the wellestablished dynein inhibitor EHNA (Penningroth et al, 1982;Reynolds et al, 1998) and the kinesin inhibitor aurintricarboxylic acid (AA) (Hopkins et al, 2000). AA has been recently identified via a structure-based computer screening for kinesin-binding molecules using human conventional kinesin as template (Hopkins et al, 2000). It has been shown to have a broad specificity for members of the kinesin superfamily (conventional kinesin, ncd C-terminal kinesin and Unc104/KIF1) (Vale, 2003) and an IC50 in the low micromolar range (0.5-1.4 µM), which is comparable to that of the only other known kinesin inhibitor, adocia sulfate-2 (Sakowicz et al, 1998).…”
Section: Efficient Tent Hc Retrograde Transport Relies On Multiple Mtmentioning
confidence: 99%
“…The molecular docking application DOCK [15] was chosen for being a nearly all-in-one virtual screening solution and because of its past successes in identifying effective inhibitory molecules [2,16]. Other appealing features of the DOCK software package are the inclusion of a number of different docking algorithms, which allows for consensus scoring, and the MPI functionality.…”
Section: Dockmentioning
confidence: 99%
“…Virtual screening presents the capability to prescreen vast databases, such as the Zinc compound library, a 13 million compound virtual database [208], by targeting a three dimensional structure to determine those compound which best fit, or dock, into a chosen allosteric or ligand binding site. This method has proven successful in the identification of a wide variety of targets [209][210][211][212][213][214][215][216][217][218][219][220][221][222][223][224][225].…”
Section: Virtual Screening As a Methods For Drug Discoverymentioning
confidence: 99%
“…Photolabeling studies of radiolabeled T140 identified TM4 as the most important segment of CXCR4 involved in binding [207]. [212], retinoic acid receptor [213], farnesyl transferase [214], kinesin [215], hypoxanthine-guanine-xanthine phosphoribosyl transferase [216], DNA gyrase [217], H IV -1 RNA transactivation response element [218], aldose reductase [219], rac GTPase [220], checkpoint kinase-1 [221], alpha amylase [222], BCR-ABL tyrosine kinase [223], protein kinase CK2 [224], and alpha-reductase [225]. In one documented case virtual screening targeting DNA gyrase identified lead compounds where experimental high throughput screening of libraries was unsuccessful [181,217].…”
Section: Structure Based Drug Design Is An Effective Technique For Idmentioning
confidence: 99%